Investigation of the native starch-ethyl cellulose film coating for colon targeting - Esmael,Mohamed; Majid,Ali (2016)
The aim of this study was to optimize a function starch-ethyl cellulose film for targeting the therapeutically active substance to the colon in the disease state for patients suffering from inflammatory bowel diseases. This study includes: • The preparation of the polymeric films and the investigation of the characterization (for example mechanical properties, water uptake, dry mass loss, and microscopy analysis) for these prepared film coatings. • Coating of the pellets with 3-1 as well as 3-2 and the study of the release through the coated pellets. • The study of the film formulation factors such as (formulation temperature, amount of the TEC, and polymer blends ratio) and their impact on the properties of the final prepared film as well as on the drug release from the coated pellets at healthy as well as disease state before and after upon exposure to: § Gastric fluid with pepsin § Intestinal fluid with and without pancreatin § Colonic fluid at different PH (6.8, 5.6, and 2.8) with different concentration of bacterial amylase.
Keywords: starch; colon delivery; pharmaceutical technology; läkemedelsteknologi